Consumption Patterns and Self-selecting Tariffs - Train, Kenneth E.; Ben-Akiva, Moshe; Atherton, Terry (The Review of Economics and Statistics, 1989)
The authors describe and apply methods for empirically investigating the relation between consumption and tariff choice. These methods allow (1) testing of alternative specifications for the relations of tariff choice and consumption patterns, (2) estimation of parameters that provide information on the response of customers to marginal prices and fixed fees, and (3) a determination of the extent to which the assumptions embodied in welfare results on self-selecting tariffs are valid in a particular setting. They apply the procedures to residential demand for local telephone service in an area where households are offered a choice among tariffs. Copyright 1989 by MIT Press.